2008
DOI: 10.1002/qj.316
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Arctic ozone loss in winter 2004/05 based on assimilation of EOS MLS and SBUV/2 observations

Abstract: ABSTRACT:In this paper we present a new technique for the estimation of ozone loss in the stratospheric polar vortex based on the assimilation of Earth Observing System Microwave Limb Sounder (EOS MLS) and Solar Backscatter Ultraviolet radiometer (SBUV/2) ozone observations in the Met Office data assimilation system. We focus on the northern winter of 2004/05, which was exceptionally cold in the Arctic stratosphere, with associated large ozone depletion due to heterogeneous chemistry. Our ozone loss estimate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
35
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 32 publications
5
35
1
Order By: Relevance
“…The stricter 10 % sPV variability criterion (grey line) also increases our estimated loss, though to a much lesser degree. Estimates of peak ozone loss that winter from all the studies shown here range from around 1.0 ppmv (our study, as well as Rösevall et al, 2008 andOrsolini, 2008), to as high as 2.2 ppmv (Jin et al, 2006;von Hobe et al, 2006). This wide range reflects the challenges associated with quantifying chemical ozone loss in a manner that properly accounts for transport processes.…”
Section: Comparison To Previous Estimates Of Ozone Loss In Thementioning
confidence: 82%
See 3 more Smart Citations
“…The stricter 10 % sPV variability criterion (grey line) also increases our estimated loss, though to a much lesser degree. Estimates of peak ozone loss that winter from all the studies shown here range from around 1.0 ppmv (our study, as well as Rösevall et al, 2008 andOrsolini, 2008), to as high as 2.2 ppmv (Jin et al, 2006;von Hobe et al, 2006). This wide range reflects the challenges associated with quantifying chemical ozone loss in a manner that properly accounts for transport processes.…”
Section: Comparison To Previous Estimates Of Ozone Loss In Thementioning
confidence: 82%
“…3f) on constant potential temperature surfaces gives peak loss of slightly larger than 1 ppmv at 450 K. In addition, there are indications of a secondary peak of ∼ 0.8 ppmv loss between 550 and 600 K. Previous studies of the 2004/05 winter have shown that ozone loss at these altitudes largely resulted from nitrogen-based catalytic cycles, although the studies report different magnitudes and vertical distributions for the overall loss. Grooß and Müller (2007) find as much as 1.6 ppmv loss at 600 K, while find ∼ 1.2 ppmv loss at the same altitude, and Jackson and Orsolini (2008) report only ∼ 0.4 ppmv loss. Section 4 discusses in more detail how our results compare with estimates from previous studies.…”
Section: Estimating Integrated Ozone Losses For Each Winter/springmentioning
confidence: 93%
See 2 more Smart Citations
“…In this paper, we employ the data assimilation technique developed for other Arctic winters by Rösevall et al (2007aRösevall et al ( , b, 2008 to investigate the ozone depletion in the 2009/2010 winter using SMILES ozone data. Other similar studies have used various models and assimilation methods (El Amraoui et al, 2008;Jackson and Orsolini, 2008;Søvde et al, 2011). One advantage of data assimilation is that it allows us to optimally use all measurements and is useful for interpolating or extrapolating the ozone distributions when and where no measurements are available.…”
mentioning
confidence: 99%